If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + x = -48 Combine like terms: -9x + x = -8x -8x = -48 Solving -8x = -48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-8'. x = 6 Simplifying x = 6
| 5(3x-6)=-(x+7)+2x | | y+9=2y-60 | | y+3=x+6 | | 2y-60=y+9 | | x^4-4x^3-x-2=0 | | 2*-3-7y=17 | | Y+2=-5(x-1) | | 15+8t=3t | | 8r=3t+4 | | 1.96g-12=0.74 | | -5w^3-4w^2+7w+16=3 | | 3x-15+2x+25=180 | | 31.61=6g+3.65 | | 4.3=5.1-0.2x | | 2n^2+n-13=-3 | | 11n^2-6N+4=7 | | 5(4*7)+x=5 | | 50=-3x-7 | | 5.9=6.5-0.3x | | ln(4x)+ln(x)=1.5 | | 3(6-x)=30 | | -4+2a=10 | | 4+2a=10 | | -13n-67=-11 | | x^2+3x-c=0 | | 83=8w+35 | | 4u+15=75 | | .06(x)=3142 | | 18.5=-7.2f+97.7 | | 7x-10y=12 | | 2x+7x=20 | | 8(x-2)=2(2x-2) |